The Influence of Work Environment, Organizational Culture and Work Motivation on Employee Job Satisfaction at CV Nadhia Karya, Kendal Regency - Oktaviani Oktaviani; Teti Safari; Endro Pramono; Ninik Dwi Atmini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this study is to explain the effect of work environment, organizational culture, and work motivation on employee job satisfaction of CV Nadhian Karya Kendal Regency. To determine the indirect effect of work environment, organizational culture, and work motivation on employee job satisfaction through the work environment. This research is a type of explanatory research, and this research approach is based on a quantitative research approach. CV Nadhia Karya Kendal Regency has a population of 120 employees, a sample of 100 and uses probability sampling techniques with random sampling techniques. Data collection was carried out using a questionnaire. The results of this study indicate that: (1) Work Environment variables have a significant influence on Job Satisfaction. This is evident in the t test results showing the t count value is greater than the t table, namely 2.025 > 1.985 and the significance value (Sig.) 0.046 < 0.05. (2) Organizational Culture variables have a significant influence on Job Satisfaction. This is evident in the t test results showing the tcount is greater than the ttable, namely 4.673> 1.985 and the significance value (Sig.) 0.000 <0.05. (3) Work Motivation variable has a significant influence on Job Satisfaction. This is evident in the t test results showing the tcount is greater than the ttable, namely 4.193> 1.985 and the significance value (Sig.) 0.000 <0.05. (4) Work Environment, Organizational Culture and Work Motivation variables on Job Satisfaction have a joint effect because they have a significant value (Sig) 0.000 <0.05.